Foreigners under Mao western lives in China, 1949-1976 - Hooper, Beverley (Hong Kong University Press, 2016)
"A pioneering study of the Western community during the turbulent Mao era. Based largely on personal interviews,memoirs, private letters, and archives, this book 'gives a voice' to the Westerners who lived under Mao. It shows that China was not as closed to Western residents as has often been portrayed."